Relationship between neutrophil gelatinase-associated lipocalin, cardiac biomarkers, inflammation index and renal parameters in cardiovascular disease - Choi, Jong Weon; Lee, Moon Hee; Fujii, Tatsuyoshi (Archives of Biological Sciences, 2019)
Paper description: There are few studies examining the contribution of myocardial injury, inflammation severity and impaired renal function to elevated plasma neutrophil gelatinase-associated lipocalin (NGAL) level in myocardial infarction (MI). Patients with MI were evaluated using the corrected values of NGAL, including the NGAL/inflammation index ratio and the NGAL/serum creatinine ratio. The severity of inflammation played a more crucial role than renal and myocardial dysfunction in affecting plasma NGAL levels in patients with MI. Our results may contribute to the evaluation of MI, particularly in patients with concurrent inflammation and renal dysfunction. Abstract: The plasma neutrophil gelatinase-associated lipocalin (NGAL) level is elevated in myocardial infarction (MI) and affected by inflammation and kidney function. The aim of this study was to determine which of these conditions more critically affects the plasma NGAL level in MI. Patients with MI were evaluated by measuring the NGAL concentration and its corrected values. No significant association was observed between plasma NGAL concentration and cardiac biomarkers. However, the NGAL/inflammation index ratio (NGAL/Inf ratio) was positively correlated with troponin-I (r=0.289, p<0.001), and the NGAL/serum creatinine ratio (NGAL/sCr ratio) was significantly correlated with creatine kinase-MB (r=0.251, p<0.001). After adjusting for inflammation and kidney function, increased NGAL concentrations returned to baseline levels, which were not different from those of healthy individuals. The percent difference between NGAL and the NGAL/Inf ratio was 35.6%, significantly higher than that between NGAL and the NGAL/sCr ratio (15.4%; p<0.001). The severity of inflammation seems to play a more crucial role than renal and myocardial dysfunction in affecting plasma NGAL levels in MI. Plasma NGAL levels need to be corrected using the inflammation index and sCr levels for exactly evaluating patients with MI. https://doi.org/10.2298/ABS190604044C Received: June 4, 2019; Revised: July 15, 2019; Accepted: July 23, 2019; Published online: July 29, 2019 How to cite this article: Choi JW, Lee MH, Fujii T. Relationship between neutrophil gelatinase-associated lipocalin, cardiac biomarkers, inflammation index and renal parameters in cardiovascular disease. Arch Biol Sci. 2019;71(4):621-8.